2017
DOI: 10.1189/jlb.3mr0617-250r
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of inflammasome signaling

Abstract: The inflammasome is a macromolecular protein complex that mediates proteolytic cleavage of pro-IL-1β and -IL-18 and induces cell death in the form of pyroptosis. Certain nucleotide-binding oligomerization domain-like receptors (NLRs), absent in melanoma 2 (AIM2)-like receptors (ALRs), or tripartite motif (TRIM) family receptors trigger the assembly of an inflammasome in response to pathogen-associated molecular patterns (PAMPs) or danger-associated molecular patterns (DAMPs). Recent studies have revealed a mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
127
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(129 citation statements)
references
References 313 publications
(857 reference statements)
1
127
0
1
Order By: Relevance
“…Since NLRP1 was first described to form the inflammasome in 2002 (Martinon et al, ), members of the NLR family (NLRP1, NLRP3, and NLRC4) as well as other proteins (AIM2, pyrin) have been confirmed to initiate formation of inflammasomes (Broz & Dixit, ; Mathur et al, ). There are also other less well‐characterized PRRs, such as NLRP2, NLRP6, NLRP7, NLRP9b, NLRP12, IFN‐γ‐inducible protein 16 (IFI16), and retinoic acid‐inducible gene I (RIG‐I; also known as DDX58) which have also been reported to activate caspase‐1 (Broz & Monack, ; von Moltke et al, ; Broz & Dixit, ; Man & Kanneganti, ).…”
Section: Targeting Inflammasome Activation In Retinal Degenerative DImentioning
confidence: 99%
“…Since NLRP1 was first described to form the inflammasome in 2002 (Martinon et al, ), members of the NLR family (NLRP1, NLRP3, and NLRC4) as well as other proteins (AIM2, pyrin) have been confirmed to initiate formation of inflammasomes (Broz & Dixit, ; Mathur et al, ). There are also other less well‐characterized PRRs, such as NLRP2, NLRP6, NLRP7, NLRP9b, NLRP12, IFN‐γ‐inducible protein 16 (IFI16), and retinoic acid‐inducible gene I (RIG‐I; also known as DDX58) which have also been reported to activate caspase‐1 (Broz & Monack, ; von Moltke et al, ; Broz & Dixit, ; Man & Kanneganti, ).…”
Section: Targeting Inflammasome Activation In Retinal Degenerative DImentioning
confidence: 99%
“…The current view is that GBP chr3 -mediated release of Gram-negative bacteria results in contamination of the cytoplasm with lipopolysaccharide (LPS), which causes robust activation of the LPS sensor caspase-11 (Meunier et al, 2014). Caspase-11 then triggers pyroptosis and activation of the NLRP3 inflammasome, an innate immune signalling complex that mediates secretion of the pro-inflammatory cytokines IL-1β and IL-18 Mathur, Hayward, & Man, 2017).…”
Section: Functions On the Host Membrane And The Pathogen-containingmentioning
confidence: 99%
“…The current view is that GBP chr3 ‐mediated release of Gram‐negative bacteria results in contamination of the cytoplasm with lipopolysaccharide (LPS), which causes robust activation of the LPS sensor caspase‐11 (Meunier et al, ). Caspase‐11 then triggers pyroptosis and activation of the NLRP3 inflammasome, an innate immune signalling complex that mediates secretion of the pro‐inflammatory cytokines IL‐1β and IL‐18 (Man & Kanneganti, ; Mathur, Hayward, & Man, ). Furthermore, GBP chr3 are required for caspase‐11‐induced pyroptosis in IFN‐γ‐treated BMDMs in response to cytosolic delivery of LPS derived from the Gram‐negative bacterium Legionella pneumophila (Pilla et al, ), suggesting that GBP chr3 may also facilitate translocation of free LPS into the cytoplasm or promote oligomerisation and activation of caspase‐11.…”
Section: Introductionmentioning
confidence: 99%
“…Many view IL-1β as the quintessential proinflammatory mediator in acute and chronic inflammation and one of the most powerful inducers of the innate immune response [5,91,92]. The inflammasome, a source for IL-1β, is a primary driver of inflammation and is best characterized in macrophages [9,25,45,46,93], but is present in other cell types, including epithelial cells [94] and neutrophils [95,96]. Neutralization of IL-1β by a monoclonal antibody in the Canakinumab for Atherosclerotic Disease (CANTOS) trial recently demonstrated that reduction of inflammation without concomitant change in lipid levels reduces the risk of atherothrombosis [13], and is strong evidence pointing to the broad reach of inflammation, especially a pathologic role for IL-1β in cardiovascular disease.…”
Section: Inflammation and Inflammasomesmentioning
confidence: 99%